OUR NATIONAL TRADITIONS AND THEIR EDUCATIONAL SIGNIFICANCE IN EDUCATING YOUNG PEOPLE IN THE SPIRIT OF MILITARY PATRIOTISM (Archive of Conferences, 2021)
In this article, we will discuss the courage and perseverance of our ancestors for the prosperous life of the future ovlod, which we have shown by putting their lives at risk, to educate the younger generation with the permission of patriotism through our inherited national traditions, to form a sense of love and loyalty to the motherland, moral and spiritual values and patriotism, considered.